Adaptive energy efficient data center model - Mohd Nor, Norhashimi; Selamat, Mohd Hasan (Science and Knowledge Research Society, 2015)
Data centers had been evolving progressively since the first supercomputer invention. Although the main functions remain the same, the goals and characteristics change parallel with technology and market demands. Characteristics that perfectly suited data centers in the 90’s or even early new millennium are no longer valid nowadays. Computing nodes or servers are gradually transforming into energy hunger machines as a consequence of being powerful. Therefore energy efficient data center came into the picture to resolve the issue in order to reduce world’s carbon footprints and ensuring sufficient energy for the next generation. However the existing energy efficient data centers are portrayed in exclusive approaches which are costly and complicated hence hindering solid data centers stakeholders participation. Thus the aim of this paper is to highlight simple and economical attributes of energy efficient data centers. The attributes focus on aspects that are free of charge (FOC), require minimal capital expenditure (CapEx) and involve minimal operating expenditure (OpEx) with continuous efforts. These attributes were extracted from five existing energy efficient data center frameworks and fused into an adaptive energy efficient data center model. The model is represented in an appealing and implementable approach to promote green awareness implementation among data center stakeholders. Additionally, the model could be the starting point for small and medium sized, existing and new data centers in adopting hassle free green initiatives with hardly any extra investment.